Appointment of Children Based on Government Regulation Number 54 Year 2007 in Human Rights Perspective - Ida Ayu Sadnyini; Ni Putu Sawitri Nandari; Ida Ayu Ketut Artami; Clara Tia Sukma Sari (Fakultas Hukum, Universitas Warmadewa, 2022)
Adoption in general is an act of taking someone else's child based on legal provisions that apply to the community concerned. Based on the determination number: 597/Pdt.P/2020/PN Dps and number: 924/Pdt.P/2019/PN Jkt Sel. It is known that there are adoptive parents who already have two biological children, this of course is not in accordance with Government Regulation Number 54 ofx2007 concerning the Implementation of Adoption. The problem in this research is that the cause of adoption is not in accordance with Government Regulation No. 54 ofx2007 and adoption from the perspective of Human Rights. The theory used in the analysis is the theory of justice, distributive justice, which is the balance between what a person gets and what he deserves. This type of research used in this paper is a type ofxnormative legal approach. The cause ofxado ption in this case is because the biological parents cannot fulfill the child's rights, so that the adoption of the child is carried out so that the fulfillment of the child's rights is fulfilled by the adoptive parents. Children's rights have a relationship with human rights and are regulated by the state.Therefore, there needs to be good cooperation between the government and the community through outreach, counseling and assistance activities in order to increase understanding of the requirements, procedures and fulfillment of children's rights in the implementation of adoption. The implementation of adoption explains that one of the requirements for prospective adoptive parents is not having children or only having one child, However, in its implementation, there was a judge's decision that allowed prospective adoptive parents who had biological children before adopting a child. So, There needs to be an update or amendment to the regulations regarding the requirements for adoption, which should prioritize the fulfillment of children's rights.